2007
DOI: 10.1136/oem.2006.030643
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to prevent back pain and back injury in nurses: a systematic review

Abstract: A systematic literature review was undertaken to assess the effectiveness of interventions that aim to prevent back pain and back injury in nurses. Ten relevant databases were searched; these were examined and reference lists checked. Two reviewers applied selection criteria, assessed methodological quality and extracted data from trials. A qualitative synthesis of evidence was undertaken and sensitivity analyses performed. Eight randomised controlled trials and eight non-randomised controlled trials met eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
138
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 48 publications
6
138
0
4
Order By: Relevance
“…Work-related pain, however, has not been a common choice as a pain measure in intervention or prevalence studies. According to a systematic review of back injury intervention studies among nurses (Dawson et al, 2007), seven out of eight studies that evaluated patient handling devices or ergonomics training assessed pain as the outcome measure, and only one study asked about work-related pain and it was the only study that found a significant reduction in pain (Yassi et al, 2001). Employing an outcome measure with an adequate sensitivity and specificity should be an important consideration in intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…Work-related pain, however, has not been a common choice as a pain measure in intervention or prevalence studies. According to a systematic review of back injury intervention studies among nurses (Dawson et al, 2007), seven out of eight studies that evaluated patient handling devices or ergonomics training assessed pain as the outcome measure, and only one study asked about work-related pain and it was the only study that found a significant reduction in pain (Yassi et al, 2001). Employing an outcome measure with an adequate sensitivity and specificity should be an important consideration in intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of mechanical lift equipment at reducing the biomechanical load of patient-handling tasks has been supported in a controlled laboratory setting (8); however, studies offer different conclusions of the effectiveness of patient-lifting equipment (often implemented in conjunction with other intervention components) at reducing adverse MS conditions among workers in patient-care settings (15)(16)(17). A number of barriers to the use of lift equipment have been described (18)(19)(20); studies suggest mechanical patient lifts are not regularly used in patient care tasks (1,(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Um estudo sistemático sobre a dor nos enfermeiros (36) sugere que estudos randomizados controlados são necessários para se obter resultados significantes em relação à dor dos trabalhadores da saúde.…”
Section: Discussionunclassified